Biological sensitivity to context in Pakistani preschoolers: Hair cortisol and family wealth are interactively associated with girls' cognitive skills. Issue 8 (26th May 2020) - Armstrong‐Carter, Emma; Finch, Jenna E.; Siyal, Saima; Yousafzai, Aisha K.; Obradović, Jelena
Abstract: Many young children in low‐ and middle‐income countries (LMICs) face heightened risk for experiencing environmental adversity, which is linked with poorer developmental outcomes. Children's stress physiology can shed light on why children are differentially susceptible to adversity. However, no known studies have examined whether links between adversity and children's development are moderated by children's stress physiology in LMICs. The present study revealed significant interactive effects of hair cortisol concentrations, an index of chronic physiological stress regulation, and family wealth on preschoolers' cognitive skills in rural Pakistan. In a sample of 535 4‐year‐old children ( n  = 342 girls), we found significant associations between family wealth and direct assessments of verbal intelligence, pre‐academic skills, and executive functions only in girls with lower hair cortisol concentrations. Specifically, girls with lower cortisol concentrations displayed greater cognitive skills if they came from relatively wealthier families, but lower cognitive skills if they came from very poor families. There were no significant associations among boys. Results provide evidence of biological sensitivity to context among young girls in a LMIC, perhaps reflecting, in part, sex differences in daily experiences of environmental adversity.